PEMBUATAN BIOETANOL DARI SINGKONG KARET (Manihot glaziovii) UNTUK BAHAN BAKAR KOMPOR RUMAH TANGGA SEBAGAI UPAYA MEMPERCEPAT KONVERSI MINYAK TANAH KE BAHAN BAKAR NABATI - Mira Amalia Hapsari; Alice Pramashinta; Aprilina Purbasari (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Manihot glaziovii is a tuber that non-food corps, because it contains cyanide acid (HCN) which are toxic. Carbohydrate content in cassava tubers is 98,5% so it is worth to be converted to bioethanol. Bioethanol is a product of hydrolysis of starch to glucose, followed by enzymatic fermentation of glucose using yeast Saccharomyces cereviceae to ethanol. The purpose of this study is to find the optimum time and mass effect on of yeast to produced ethanol as a fuel household stoves. The research was carried out in several stages, including the enzymatic hydrolysis of cassava starch to glucose and continued fermentation of glucose to ethanol. Bioethanol purification is done by distillation process. The main tool that used is fermentor and distillation tower as a means of separating ethanol from water. Analysis of glucose levels is done by titration using Fehling A and B, while the ethanol concentration measurements with alkoholmeter. The results showed that the optimum volume was 3 mL enzyme that produces glucose level of 18% which is good for fermentation. The results that have been achieved for the fermentation time variable 144, 168 and 192 hours earned the highest ethanol content is 94% at 168 hours fermentation time, while for variable mass 5.10 yeast, and 15 g obtained the highest ethanol content is 94% in mass yeast 15 gr.